2012
DOI: 10.1007/s10493-012-9530-4
|View full text |Cite
|
Sign up to set email alerts
|

A review of the ticks (Acari: Ixodida) of Turkey: species diversity, hosts and geographical distribution

Abstract: Ticks are important ectoparasites, causing a variety of serious infectious diseases in humans and domestic animals. There is very limited taxonomic information about the tick species of Turkey in the literature, even though Turkey has very suitable climate and vegetation for ticks. In the current study, species diversity, hosts and geographical distribution of the ticks present in Turkey are reviewed based on taxonomic data in the literature from 1915 to 2011 and our recent observations. The names of tick spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 21 publications
(47 reference statements)
3
57
0
4
Order By: Relevance
“…Among factors that affect tick infestation rate are not only geographical floral features of regions but also climate is very important for ticks' proliferation (Bursali et al, 2012). Also, none of the species of the ticks cause viremia though out all the year (Bursali et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among factors that affect tick infestation rate are not only geographical floral features of regions but also climate is very important for ticks' proliferation (Bursali et al, 2012). Also, none of the species of the ticks cause viremia though out all the year (Bursali et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Also, none of the species of the ticks cause viremia though out all the year (Bursali et al, 2012). Some studies that were hold in Turkey to determine periodic intensity of tick infestations stated that the most intense month is August (Gargili et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although Turkey's tick fauna consist of 46 species, 38 species within Ixodidae family, Hyalomma, Haemaphysalis, Rhipicephalus, Dermacentor and Ixodes genus have medical and veterinary importance [1,2] . Previous studies performed on ruminants indicated the existence of different tick species in six genus in Bursa province [6] .…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal activity, prevalence, and intensity of these ticks are not well known [1,2] . Twenty two tick species were identified on ruminants and other wild domestic animals in Marmara region [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Kenelerin naklettiği 200 kadar patojen arasında protozoon, virus, bakteri, riketsia ve helmint türleri yer almaktadır (18,26). Bu hastalıkların naklinde rol oynayan bazı kene soylarına (Ixodes, Haemaphysalis, Dermacentor, Boophilus, Hyalomma, Rhiphicephalus, Ornithodorus) ait türler Türkiye'de yaygın olarak evcil hayvanlarda görülmektedir (4,5,9,20 (1,6,7,8,19,25,28).…”
Section: Introductionunclassified